Relationship between design thinking and entrepreneurial way of doing business: case of a brazilian crossfit academy (Dimensión Empresarial, 2022)
This study aims to apply the Design Thinking tool to understand Crossfit practitioner expectations of a business unit located in a Brazilian state. Through an exploratory study develops the prototyping of the design of a box and a co-creation for the formulation of a positioning panel. They were presented as solutions that support the decision to stay in the affiliate as well as winning new members the creation of Custom Training. Understanding consumer behavior, of course, will help a CrossFit Boxing entrepreneur to successfully combine business positioning with the practitioner's happiness and health.
Keywords: co-creation; training; Entrepreneurship; position